2019
DOI: 10.1111/dom.13794
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial comparing the efficacy and safety of treating patients with type 2 diabetes and highly elevated HbA1c levels with basal‐bolus insulin or a glucagon‐like peptide‐1 receptor agonist plus basal insulin: The SIMPLE study

Abstract: Aim: To compare the efficacy and safety of a glucagon-like peptide-1 receptor agonist (GLP1RA) plus basal insulin versus basal-bolus insulin treatment in patients with very uncontrolled type 2 diabetes. Materials and methods:The SIMPLE study was a 6-month pragmatic, randomized, open-label trial testing the effectiveness of two approaches to treat patients with type 2 diabetes and HbA1c ≥10%. We randomized patients to detemir plus liraglutide or detemir plus aspart (before each meal). The primary endpoint was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This is an analysis of the SIMPLE study, which was a prospective, randomized, open-label, parallel group trial comparing two treatment strategies (GLP1RA+BI vs BBI), both in addition to metformin in individuals with very uncontrolled (HbA1c≥10%) T2D. The intention-to-treat data set of the SIMPLE trial included n=110 with 54 patients in GLP1RA+BI group and 56 patients in the BBI group 18…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is an analysis of the SIMPLE study, which was a prospective, randomized, open-label, parallel group trial comparing two treatment strategies (GLP1RA+BI vs BBI), both in addition to metformin in individuals with very uncontrolled (HbA1c≥10%) T2D. The intention-to-treat data set of the SIMPLE trial included n=110 with 54 patients in GLP1RA+BI group and 56 patients in the BBI group 18…”
Section: Methodsmentioning
confidence: 99%
“…The dose was titrated to maximum tolerated dose or to 1000 mg twice daily. A full description of the study design, interventions, and outcomes can be found in the primary manuscript 18…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations